Pengaruh Perlakuan Rizo-bakteri Pemacu Pertumbuhan Tanaman terhadap Viabilitas Benih serta Pertumbuhan Bibit Tanaman Cabai - Gusti Ayu Kade Sutariati; Widodo Widodo; Sudarsono Sudarsono; Satriyas Ilyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
The objectives of this experiment were to evaluate effects of seed treatment using local isolates of rhizobacteria on seed germination and seedling growth of hot pepper. Hot pepper seeds were treated with rhizobacterium isolates of Bacillus sp., Pseudomonas sp., or Serratia sp. and germinated using standard germination procedures. Subsequently, seedlings were transplanted into plastic pots containing a mixture of potting media. Germination was recorded at 7 and 14 days while seedling growth were recorded at 6 and 8 weeks after transplanting. Results of the experiments showed seed treatments using rhizobacteria significantly increased viability of the treated hot pepper seeds (percentage of increases as compared to untreated seeds in seed germination  - up to 27%, PTM 11%, vigor index 31%, SPT 29%, KCT 29%, and reduction of T50 by 0.75 days). Some of the treatments also promoted growth of hot pepper seedlings. Although all of the rhizobacteria synthesized IAA, growth promoting effects of the rhizobacteria may not only be due to the synthesized growth regulator. Other factors may have involved in the possitive effects of the rhizobacteria on hot pepper seed germination and seedling growth.   Key words:  Rhizobacteria, indole-acetic acid, PGPR, vigor, viability, seedling growth